1997
DOI: 10.1038/sj.bmt.1700677
|View full text |Cite
|
Sign up to set email alerts
|

Late onset haemolysis and red cell autoimmunisation after allogeneic bone marrow transplant

Abstract: Summary:would be expected for non-BMT patients. The patients reported here fall into two groups, an early onset group associated with cold autoantibodies and a late onset group We reviewed the medical records of 293 patients who underwent allogeneic bone marrow transplants at the associated with warm antibodies. In the early group the antibodies occurred between 2 to 8 months and in the late Hammersmith Hospital between 1989 and 1994. There was clinical evidence of an autoimmune reaction against onset group be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
113
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(122 citation statements)
references
References 2 publications
7
113
0
2
Order By: Relevance
“…2,13,14 Only in the study by Page et al, 15 a substantially higher frequency was reported; however, this study focused on very young infants that were transplanted for nonmalignant diseases. These two factors were recently associated with an increased risk of autoimmune disorders after UCBT.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…2,13,14 Only in the study by Page et al, 15 a substantially higher frequency was reported; however, this study focused on very young infants that were transplanted for nonmalignant diseases. These two factors were recently associated with an increased risk of autoimmune disorders after UCBT.…”
Section: Discussionmentioning
confidence: 77%
“…This is surprising and seems to be different to what was previously reported. In fact, most series have described a predominance of IgG warm antibodies directed against antigens of the rhesus system, 14,19,20 whereas Chen et al 13 suggested that the presence of IgM antibodies was restricted to AIHA with early onset. We do not have a definite explanation for the above mentioned findings, but they could be due to a delayed and singular humoral reconstitution after UCBT compared with that seen with BMT.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune hemolysis is reported [4][5][6][7][8] to occur at a median of 7 months post transplant, 40/56 AIHA were of warm-type IgG, remission of hemolysis was reported in only 16 patients (pharmacological treatment [4][5][6][7][8] ) and in six patients who received a second hematopoietic SCT or DLI 4,8 for disease relapse or graft failure. AIHA occurred exclusively 4,5,8 or preferentially 6,7 in unrelated hematopoietic SCT.…”
mentioning
confidence: 99%
“…AIHA occurred exclusively 4,5,8 or preferentially 6,7 in unrelated hematopoietic SCT. Children o10 years and children transplanted for metabolic disorders had an increased risk for AIHA, 4 as had adults with extensive chronic GVHD, 5,7 whereas T-cell depletion, ABO mismatch and CMV status were not risk factors.…”
mentioning
confidence: 99%
“…Compared with the incidence of one to two cases per 100 000 in the normal adult population, 1 AIHA is estimated to occur in 3-5% of adult HSCT patients. 2,3 In the largest study of pediatric patients to date, published in 2004, the incidence of all types of AIHA was 6% at 1 year after transplant. 4 The cause for this increased incidence post transplant is poorly understood, but is likely because of an incomplete reconstitution of the immune system and immune dysregulation.…”
mentioning
confidence: 99%